Evaluating the Distribution of Porcine Epidemic Diarrhea Virus, Porcine Reproductive and Respiratory Syndrome Virus, and Seneca Valley Virus 1 Inoculated Feed After the Use of Physical or Chemical Mitigants to Flush a Feed Manufacturing Facility - Olivia L. Harrison; Haley K. Otott; Jianfa Bai; Vaughn A. Hamill; Aaron Singrey; Phillip C. Gauger; Marcelo N. Almeida; Jason C. Woodworth; C. R. Stark; Roman M. Pogranichniy; Cassandra K. Jones; Jordan T. Gebhardt; et al. (Kansas Agricultural Experiment Station Research Reports, 2023)
Contaminated feed is a route of virus transmission between feed mills and swine farms. To reduce the risk of transmission, an understanding of the virus distribution and mitigation strategies are needed. The objective of this study was to evaluate the distribution of porcine epidemic diarrhea virus (PEDV), porcine reproductive and respiratory syndrome virus (PRRSV), and Seneca Valley virus 1 (SVV1) inoculated feed in the environment and feed of a feed mill before and after the use of chemical mitigants. A 50-lb batch of feed was run through a mixer and bucket elevator followed by a batch inoculated with PEDV, PRRSV, and SVV1. Following the virus-inoculated batch, a flush treatment of either 1) ground corn (GC); 2) GC + 1.5% liquid formaldehyde (LF; SalCURB LF Liquid, Kemin, Des Moines, IA); 3) GC + 1.5% LF + 25% abrasive material (SalCURB; Shell & Bone Builder, Iowa Limestone Company, Urbandale, IA); 4) double flush – GC + 25% abrasive material followed by GC +1.5% LF (Shell & Bone Builder; SalCURB); or 5) dry formaldehyde (SalCURB F2 Dry, Kemin, Des Moines, IA) was utilized, followed by 3 virus-free batches of complete feed. Feed and environmental samples were collected from each piece of equipment following every batch. Dust samples were collected after manufacturing from the inoculated, flush, and final batches from non-feed contact surfaces. Non-feed contact surfaces were considered those where dust would accumulate during manufacturing but would not be included in the final diet. The surfaces included the grates of the mixer, the top of the discharge bin following the bucket elevator, and the floor surrounding the same discharge bin. Samples were analyzed via a triplex PCR at the Kansas State University Veterinary Diagnostic Laboratory. A treatment × batch × location interaction was not observed (P>0.05) in feed or the environment for any of the viruses. A flush treatment × batch interaction was observed for SVV1 where greater quantities of viral RNA (P<0.05) were present in the positive batches and the ground corn flush than in those batches which used chemical mitigants or the post-flush batches. A lower quantity of viral RNA (P<0.05) in dust was observed in the last batch of feed compared to the inoculated batch for all viruses; however, SVV1 RNA was still detectable in the dust following the last batch in all treatments. A batch effect (P<0.05) was observed in all sample matrices for PEDV and PRRSV as viral RNA decreased after the implementation of the flush regardless of treatment. The use of chemical mitigants and the implementation of a flush batch reduced the quantity of viral RNA for PEDV, PRRSV, and SVV1. However, viral presence was still observed in feed and the dust on non-feed contact surfaces which could be a source of contamination if re-introduced into finished feed.
Keywords: viruses; feed mills; chemical; mitigation; PEDV; PRRSV